Acute neuromuscular and perceptual responses to U-18 English Premier League academy football match play - Springham, M.; Singh, N.; Stewart, P.; Matthews, J.; Jones, I.; Norton-Sherwood, C.; May, D.; Trehan Sharma, S.; Salter, J.; Strudwick, A. J.; Shaw, J. (European Journal of Sport Science, 2024)
We examined the sensitivity and time-course of recovery of neuromuscular and perceptual player monitoring measures to U-18 English Premier League academy football match play. Eighteen players performed maximal posterior chain, hip adductor and abductor isometric strength tests, countermovement jumps (CMJ) and provided self-report wellbeing scores around eight competitive league home games: 1 day before (MD-1), pre-match (MD-PRE), post-match (MD-POST) and two (MD+2) and three (MD+3) days post-match. A permutational multivariate analysis of variance and post hoc univariate analyses of variance were used to examine match-induced responses to monitoring variables. Between MD-1 and MD-POST, we observed small to moderate reductions to the adductor and abductor peak force and maximal impulse and IPCS peak force; small reductions to CMJ jump height (JH) (flight time), eccentric peak force and eccentric deceleration rate of force development and moderate to large reductions to perceived fatigue, muscle soreness and mood. No match-induced changes were observed for CMJ flight time: contraction time or eccentric duration. Posterior chain, abductor, CMJ and self-report measures normalised by MD+3 but adductor peak force remained compromised at MD+3 (ES = small). Posterior chain, adductor and abductor peak isometric force and maximal impulse; CMJ JH, eccentric peak force and eccentric deceleration rate of force development and perceived fatigue, muscle soreness and mood are sensitive to match-induced fatigue. Since adductor peak force remained compromised at MD+3, it is apparent that players might not achieve complete neuromuscular recovery within 3 days of match play, and that the adductor muscle group might be particularly vulnerable to match-induced fatigue.